Physicists in Cracow – on the 70th anniversary of the First International Cosmic Rays Conference - Maria Pawłowska (Studia Historiae Scientiarum)
The article discusses an extraordinary event, i.e. the First International Cosmic Rays Conference, which took place in Cracow in 1947, shortly after the end of the Second World War. The conference was organized by a group of theoretical physicists from the Jagiellonian University and the Academy of Mining under the leadership of Professor Jan Weyssenhoff. The achievements of Polish physicists, especially Cracow scientists, who were involved in the study of cosmic radiation in the 1930s and 1940s are reminded of in this article. The author recalls names of outstanding physicists representing the most wellknown research centers in Europe and the United States during the Conference. The article was enriched with photographs taken during the Conference and numerous unofficial meetings that took place in October 1947 in Cracow. The author of the pictures, Andrzej Hrynkiewicz, was a young scientist, and later professor of nuclear physics at the Jagiellonian University and the Institute of Nuclear Physics of the Polish Academy of Sciences.